Colloidal HPMO Nanoparticles: Silica‐Etching Chemistry Tailoring, Topological Transformation, and Nano‐Biomedical Applications. (15th February 2013) - Chen, Yu; Xu, Pengfei; Chen, Hangrong; Li, Yongsheng; Bu, Wenbo; Shu, Zhu; Li, Yaping; Zhang, Jiamin; Zhang, Lingxia; Pan, Limin; Cui, Xiangzhi; Hua, Zile; et al.
<x xml:space="preserve">Abstract</x> Hybridization produces the better: Colloidal hollow periodic mesoporous organosilica nanoparticles (HPMO NPs) with tunable compositions and highly hybridized nanostructures are successfully synthesized by a simple, easily scale‐up but versatile silica‐etching chemistry (alkaline or HF etching) for their applications in nano‐fabrication and nano‐medicine. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>